WHATSAPP GROUP AND GOOGLE CLASSROOM-BASED LEARNING MATERIALS IN ENGLISH CLASSES: STUDENTS’ PERCEPTIONS - Irma Rasita Gloria Barus; Marudut Bernadtua Simanjuntak (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2020)
The aim of this study is to explore the students’ perception of the use of WhatsApp Group and Google Classroom-based learning in English classes at College of Vocational Studies - IPB University, Bogor. The study was taken for the applied multimedia learning system by the teachers as the authors of this paper. The data were taken from questionnaires of the students’ perception of the implemented based learning by using Likert scale. The scoring system was done by recommended and an un-recommended points. The data were analyzed descriptively using table scoring of percentage 1-100 aiming at the students’ points of view or opinions. The result of this study which was focused on learning material in English classes proves that the students agree that this based learning is effective to be applied and used. The average score of perceptions is 89 indicated from the six components of the product (comfortability, content, efficient use, language, clarity, and fun-use).